2018
DOI: 10.1016/j.cmet.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that TLR4 Is Not a Receptor for Saturated Fatty Acids but Mediates Lipid-Induced Inflammation by Reprogramming Macrophage Metabolism

Abstract: Chronic inflammation is a hallmark of obesity and is linked to the development of numerous diseases. The activation of toll-like receptor 4 (TLR4) by long-chain saturated fatty acids (lcSFAs) is an important process in understanding how obesity initiates inflammation. While experimental evidence supports an important role for TLR4 in obesity-induced inflammation in vivo, via a mechanism thought to involve direct binding to and activation of TLR4 by lcSFAs, several lines of evidence argue against lcSFAs being d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
290
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(309 citation statements)
references
References 78 publications
14
290
0
5
Order By: Relevance
“…It has been suggested that fatty acids activate macrophages by binding to TLR4 (339, 423). However, other evidence indicates that long chain saturated fatty acids are not direct ligands of TLR4 but rather that saturated fatty acid-induced inflammation requires an initial priming event of TLR4 (110, 258). Intriguingly, mice lacking TLR4 (a) are protected from the ability of a systemic lipid infusion to trigger insulin resistance, and (b) become obese when fed a HFD but remain relatively insulin sensitive with lower levels of inflammation in liver and adipose tissue (423).…”
Section: Adipose Tissue Inflammation In Obesitymentioning
confidence: 99%
“…It has been suggested that fatty acids activate macrophages by binding to TLR4 (339, 423). However, other evidence indicates that long chain saturated fatty acids are not direct ligands of TLR4 but rather that saturated fatty acid-induced inflammation requires an initial priming event of TLR4 (110, 258). Intriguingly, mice lacking TLR4 (a) are protected from the ability of a systemic lipid infusion to trigger insulin resistance, and (b) become obese when fed a HFD but remain relatively insulin sensitive with lower levels of inflammation in liver and adipose tissue (423).…”
Section: Adipose Tissue Inflammation In Obesitymentioning
confidence: 99%
“…Recent data show that pro-inflammatory activation of macrophages by saturated fatty acids (SFA) is independent of Toll-like receptor 4, yet the receptor that is responsible is still not known (7). 20 Recently, we have shown that in vitro activation of the phagocytic receptor, macrophage scavenger receptor 1 (MSR1, also known as SR-A or CD204), results in pro-inflammatory macrophage polarisation through JNK activation (8).…”
Section: Main Textmentioning
confidence: 99%
“…However, some PRRs protect against metabolic inflammation and insulin resistance during obesity (Denou et al 2015;Cavallari et al 2017). It has now been shown that PRRs can reprogram cellular metabolism and propagate inflammation as opposed to being direct sensors for obesity-associated inflammatory "ligands", such as saturated fatty acids (Lancaster et al 2018). There is still much to learn about how obesity-related triggers of inflammation engage elements of the immune system to alter cellular and systemic metabolism.…”
Section: Introductionmentioning
confidence: 99%